Anaerobic digestion of agro-industrial waste: Anaerobic lagoons in Latin America - Galván Arzola, Uriel; Miramontes Martínez, Luis Ramiro; Escamilla Alvarado, Carlos; Botello Álvarez, José Enrique; Alcalá Rodríguez, Mónica María; Valencia Vázquez, Roberto; Rivas García, Pasiano (Universidad Autónoma Metropolitana, 2022)
In developed countries, the valorization of agro-industrial wastes (AW) using waste-to-energy strategies through anaerobic digestion (AD) is a reality. In Latin America (LATAM), there are di erent problems in the management of AW from intensive livestock farming. This study aims to provide a pseudo-radiography of AD management systems focusing on covered anaerobic lagoons (CALs) in Latin America. Quantitative and qualitative data from 1,003 scientific papers were synthesized and analyzed to form adatabase using data science, which allowed evaluation of the congruence of the scientific research with the real problems of LATAMmanagement.Thirty-eight types of inhibition phenomena with 5,264 mentions were addressed in the database. Nitrogenrelated AD inhibition phenomena represented 21% of the incidences in this study, besides being the most significant phenomenon in covered anaerobic lagoons in LATAM. The results showed that CALs in the region are the principal AW management systems (mainly bovine and swine manure) and that scientific research in this sector does not address the real problems in the sector.